Effects of cinnamaldehyde against planktonic bacteria and biofilm formation of Shigella flexneri. (October 2022) - Zhan, Xiangjun; Tan, Yingzhu; Cheng, Xiaomeng; Wang, Renzi; Guo, Du; Wang, Muxue; Su, Ruiying; Chang, Yunhe; Xia, Xiaodong; Shi, Chao
Abstract: Cinnamaldehyde (CA) has demonstrated anti-inflammatory, anti-tumor and anti-cancer activities; Its antimicrobial and antibiofilm actions against Shigella flexneri, on the other hand, have not been investigated. Sh. flexneri is a gram-negative foodborne pathogen that can be widely found in nature and some industrial production environments. In this current research, our aim was to examine the influences of CA on planktonic bacteria and biofilm formation. The minimum inhibitory concentration (MIC) of CA against Sh. flexneri strain was 100 μg/mL, while bacteria treated with CA showed a longer lag phase compared with the untreated control. CA effectively inactivated the Sh. flexneri in LB broth and fresh lettuce juice. CA treatment resulted in cell membrane permeability changes and dysfunction, as proven by cell membrane depolarization, decreased intracellular ATP concentration. In addition, CA was also discovered to increase the level of reactive oxygen species (ROS) in cells, and induce morphological changes in cells. Crystal violet staining showed that the biomass of biofilm was decreased significantly with CA in 24 h. Light microscopy and field emission scanning electron microscopy (FESEM) observations demonstrated decreased biofilm adhesion and destruction of biofilm architecture after treatment with CA. These findings indicated that CA acts as a natural bacteriostatic agent to control Sh. flexneri in food processing and production. Highlights: The antibacterial mechanism of cinnamaldehyde (CA) on Shigella flexneri was described. CA reduced the survival of Sh. flexneri in fresh lettuce juice at a low temperature. CA caused cell membrane damage and morphological damages in Sh. flexneri. CA efficiently inhibited the formation of Sh. flexneri biofilm.